KIAI'S LEADERSHIP STRATEGY IN IMPROVING USTAZ COMPETENCE AT PONDOK PESANTREN AL- FAUZANNIYAH SUKARESMI GARUT - Bakar, Anwar Abu; Mulyanto, Agus; Suherman, Usep; Anwar, Saeful (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the leadership strategies of kiai in improving the competence of ustaz at Al-Fauzanniyah Islamic Boarding School, Garut, as a form of adaptation to the dynamics of contemporary Islamic education. The research method used is a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. The results showed that kiai leadership is transformational, which is realised through exemplary approaches, intensive mentoring, and strengthening scientific forums. This strategy strengthens the capacity of ustaz in three dimensions: science, pedagogy, and classroom management. In addition, kiai also succeeded in integrating traditional salafi values with the formal education system through an inculturative and innovative approach. Challenges include inequalities in pedagogic competence and resistance to innovation, while opportunities include increased community trust and the strategic role of alumni. This research emphasises the importance of value-based leadership and adaptive strategies to maintain the sustainability and relevance of pesantren in the national education system. The results of this study are expected to be a reference for the development of pesantren leadership models that are contextual and responsive to changing times.